(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This article was concerned local administration of Tashkent city exampling Sebzar district at the end of the XIX th and beginning of the XX th century. In article illuminated themes administration of local politics, administration of legality and controlling perspectives, as such social and material condition of population